Performance Evaluation of CMIP6 Models in Simulating the Interdecadal Variations of Summer Precipitation in Eastern China - Shuai ZHENG; Bo SUN; Wanling LI; Rufan XUE (Gaoyuan qixiang)
The summer precipitation in eastern China has significant interdecadal variaitons， which can impact the spatiotemporal variability of drought and floods as well as people’s living.Hence， it is important to understand and predict the interdecadal variations of summer precipitation in eastern China.The Coupled Model Intercomparison Project Phase 6（CMIP6） can help to understand the changes in climatic factors and predict their future changes.What is the capability of CMIP6 models in simulating the interdecadal variations of summer precipitation in eastern China？ What are the potential reasons？ In order to understand the above questions， this study evaluated the capability of CMIP6 models in simulating the interdecadal variations of summer precipitation in eastern China， using the CN05.1 observational data， ERA5 reanalysis data， NOAA sea surface temperature （SST） data and the output of historical experiments from 30 CMIP6 models.The results indicate that during 1961 -2014， the summer precpitation over eastern China underwent two notable interdecadal variations， which occurred in the mid-1970s and early-1990s.During these two interdecadal variations， the simutaneously enhanced/weakened Western Pacific Subtropical High （WPSH） and South Asian High（SAH） as well as the interdecadal change in tropical Pacific SSTs induce changes in the winds and divergence at the 850-hPa and 200-hPa pressure levels over southern China （18°N -30°N， 105°E -122°E）.The associated interdecadal changes in water vapor flux， meridional circulation and atmospheric stability in lower troposphere led to interdecadal changes in summer precipitation in eastern China.Although the CMIP6 models can well simulate the climatology of summer precipitation in eastern China， only 5 out of 30 models have relatively good capability in simulating the aforementioned two interdecadal variations in summer precipitation， which have taylor scores larger than 0.7， while the other models have relatively poor skill.In addition， the best multi-model ensemble （BMME） means show better skills in simulating these two interdecadal variations in summer precipitation than individual models.This is because the BMME can well simulate the simultaneous change in WPSH and SAH as well as the change in tropical Pacific SSTs， which leads to a good simulation of the meridional circulation over eastern China， resulting in a good simulation of the summer precipitation anomalies south of the Yangtze River.